2019
DOI: 10.1021/acs.molpharmaceut.9b00545
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Computations of Preferential Interaction Coefficients of IgG1 Monoclonal Antibodies with Sorbitol, Sucrose, and Trehalose and the Impact of These Excipients on Aggregation and Viscosity

Abstract: Preferential interactions of formulation excipients govern their overall interactions with protein molecules, and molecular dynamics simulations allow for the examination of the interactions at the molecular level. We used molecular dynamics simulations to examine the interactions of sorbitol, sucrose, and trehalose with three different IgG1 antibodies to gain insight into how these excipients impact aggregation and viscosity. We found that sucrose and trehalose reduce aggregation more than sorbitol because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 48 publications
5
42
0
Order By: Relevance
“…To gain insights into how formulation excipients of protein therapeutics affect aggregation and viscosity, Trout and coworkers conducted MD simulations using 3 different IgG1 and several carbohydrates. 135 They found that sucrose and trehalose reduced antibody aggregation more than sorbitol because of their larger size and stronger interactions with high-SAP regions of the antibodies.…”
Section: Spatial Aggregation Propensitymentioning
confidence: 99%
“…To gain insights into how formulation excipients of protein therapeutics affect aggregation and viscosity, Trout and coworkers conducted MD simulations using 3 different IgG1 and several carbohydrates. 135 They found that sucrose and trehalose reduced antibody aggregation more than sorbitol because of their larger size and stronger interactions with high-SAP regions of the antibodies.…”
Section: Spatial Aggregation Propensitymentioning
confidence: 99%
“…The pIs of mAbs A, B, and C are 9.1, 9.0, and 7.2, respectively. 11 Another study indicated that proline is a desirable excipient under stressful conditions, such as low pH, because it reduces aggregation. 39 Thus, proline's impact on conformational and colloidal stability might be dependent on formulation pH and mAb pI.…”
Section: Antibody-excipient Interactionsmentioning
confidence: 99%
“…10 One type of experimental data that can be used to validate force field parameters involving proteinexcipient-water mixtures is the preferential interaction coefficient (Γ 23 Þ. 11 Timasheff and others have studied the preferential interactions of certain sugars and polyols with small proteins using preferential interaction theory. [12][13][14] It is hypothesized that the exclusion of these osmolytes from the protein surface favors the native, folded state to minimize the exposed surface area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations